Integrative model for the biopsychosocial assessment in pediatric oncology - Olimpia Petzold; Darius Razavi (Revista Habanera de Ciencias Médicas)
Introduction: Building an evaluation model that derives from oncology pediatric patients' perspective is essential for effectively meeting their needs. Current standards of pediatric psychosocial-oncology care are mainly determined by medical providers and the child's relatives. There is a recognized need to develop a holistic model that is driven by patients themselves, with a central focus on utilizing art as a tool to facilitate the expression of their inner world.